Letter from Éamonn Duggan to his fiancée May Kavanagh, written from Navan, Co. Meath, - Duggan, Éamonn, 1874-1936 (1918)
Duggan's letter, written on headed paper of the Central Hotel, Navan, refers to his campaigning in Meath ahead of the 1918 General Election, notably at Sinn Fein events in Longwood, Summerhill and Trim, where [Maurice] Moore spoke on his behalf, and his forthcoming trip to Kells.